2020
DOI: 10.1093/cid/ciaa1345
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Responses of Neutralizing Antibodies Against Middle East Respiratory Syndrome Coronavirus (MERS-CoV) in Recovered Patients and Their Therapeutic Applicability

Abstract: Background Zoonotic coronaviruses have emerged as a global threat by causing fatal respiratory infections. Given the lack of specific antiviral therapies, application of human convalescent plasma retaining neutralizing activity could be a viable therapeutic option that can bridge this gap. Methods We traced antibody responses and memory B cells in peripheral blood collected from 70 recovered MERS-CoV patients for three years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 36 publications
4
25
0
Order By: Relevance
“…While levels of neutralizing antibodies to MERS-CoV were reported to remain stable for > 2 years (35), for SARS-CoV-2, it is now recognized, that antibody levels are already declining after 3 months (36,37). Therefore, identifying potential COVID-19 plasma donors is underlying additional time constraints.…”
Section: Discussionmentioning
confidence: 99%
“…While levels of neutralizing antibodies to MERS-CoV were reported to remain stable for > 2 years (35), for SARS-CoV-2, it is now recognized, that antibody levels are already declining after 3 months (36,37). Therefore, identifying potential COVID-19 plasma donors is underlying additional time constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the catastrophic impact of coronaviruses on public health worldwide, few effective therapeutic options are available for the diseases caused by these viruses [ 3 ]. Immune serum or plasma samples collected from recovered patients have been found to retain neutralizing activity in clinical therapeutic applications [ [4] , [5] , [6] , [7] ]. However, knowledge of the long-term dynamics and durability of specific antibody responses in recovered MERS and COVID-19 patients is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the nature of humoral immunity as a form of protective therapy remains unclear [ 8 ]. We previously found that anti-MERS-CoV spike antigen-specific IgG responses, including the neutralizing activity, and the presence of antibody-secreting memory B cells lasted up to three years after infection and were significantly correlated with disease severity [ 7 ]. In addition, sera with high neutralizing antibody titers suppressed viral replication but could not reduce excessive pulmonary inflammation during fatal infection in a transgenic mouse model [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also becoming clear that levels of specific antibody responses and opportunity to recover them in testing is significantly dependent on clinical severity and duration of viral persistence. 8 A recent study showed that anti-SARS-CoV-2 antibodies to the spike protein decreased over 60 days in healthcare personnel with 58% of seropositive individuals becoming seronegative. 9 T-cell studies found reactions to SARS-CoV2 in blood samples from people who had not been exposed to the virus suggesting the possibility of cross-reactivity with other coronaviruses, including common-cold types.…”
mentioning
confidence: 99%